Formulation Development and in-vivo/in-vitro Characterization of Novel Glucose Responsive Hydrogel for Insulin Delivery: Glucose Responsive Insulin Delivery - Saindane, Rupesh A.; Hardikar, Sharwaree R. (Iranian Journal of Pharmaceutical Sciences, 2024)
Glucose-responsive delivery systems intelligently regulate insulin release in response to fluctuating blood glucose levels, offering a more controlled approach to diabetes management. The current study introduces a novel glucose-responsive hydrogel system for enhanced insulin delivery. The hydrogel, formulated from chitosan and Poloxamer 407, exhibits unique thermo-responsive and pH-sensitive characteristics, making it suitable for subcutaneous insulin delivery. The research encompasses comprehensive in vitro and in vivo analyses to evaluate the formulation’s efficacy and responsiveness to glucose concentrations. In vitro studies demonstrated that the hydrogel’s solubilization rate varies with pH and glucose levels, crucial for controlled insulin release. Notably, the hydrogel exhibited an extended and more stable control of blood glucose levels compared to conventional insulin treatments. One significant finding is the hydrogel’s rapid in vivo gelation and biodegradability, indicating its safety and effectiveness in a physiological environment. In vivo experiments conducted on diabetic rats showcased the hydrogel’s glucose-responsive behavior. Moreover, the hydrogel’s ability to modulate insulin release in response to changing glucose levels was distinct from traditional insulin therapies, highlighting its potential to manage multiple hyperglycemic episodes after a single dose. Overall, this research marks a significant advancement in insulin delivery systems. The development of this glucose-responsive hydrogel system presents a promising approach for achieving more controlled and stable blood glucose levels in individuals with diabetes, potentially enhancing their quality of life. The findings suggest opportunities for further optimization, particularly in insulin content, to tailor the system to the specific needs of the diabetic population.